Whitman Papers, - Whitman, Marcus, 1802-1847
Artificial collection assembled by the Spokane Public Library from a variety of sources. Miscellaneous material relative to Marcus Whitman and his Wailatpu mission station. Includes Wailaptu inventory, notes about Whitman, records of the "First Presbyterian Church in the Columbia Territory," congressional report on the death of Whitman. Also includes transcripts of letters to and from Whitman. The only two original items are a letter from P. B. Littlejohn at Wailatpu, describing life at the mission in 1840, and a portion of a legal document signed by Thomas Bronchet (?), Nez Perce, and witnessed by Perrin Whitman, 1888.